The Role of Zakat and Waqf in the Development of Islamic Economics - Suriyati, Andi; Gustina, Gustina; Sumantri, Rinol (The Future of Education Journal, 2026)
Sharia economic development aims to achieve comprehensive societal welfare by emphasizing the principles of justice, balance, and welfare. However, in practice, economic development still faces various problems such as poverty and unequal income distribution. Zakat and waqf, as Islamic social financial instruments, have great potential to support sharia economic development, but their role has not been optimally utilized. This article aims to theoretically examine the role of zakat and waqf in sharia economic development. The method used in writing this article is a literature study, examining various concepts, theories, and expert views related to zakat, waqf, and sharia economic development. The results of the study indicate that zakat plays an effective role in income redistribution in reducing poverty and social inequality, while waqf plays a role in supporting long-term economic development through the provision of public facilities and improving the quality of human resources. Thus, optimizing the synergistic role of zakat and waqf can be a strategic solution in realizing equitable and sustainable sharia economic development.